Factors Influencing the Discard of Custom-made Garments among Female Students of University of Cape Coast, Cape Coast, Ghana (International Journal of Technology and Management Research, 2020)
This paper examined the factors that are likely to cause the discard of custom-made garments among female students of the University of Cape Coast. The descriptive survey design was used for the study and the total number of participants was 246.  The Predictive Analytical Software was employed for data analyses. The data gathered were analysed using inferential statistics and descriptive statistics such as frequencies and percentages. The study revealed that constructional factors form a higher percentage of the factors that lead respondents to discard their custom-made garments. The major factors that resulted in the discard of custom-made garments among the respondents were poorly stitched garments, poor fit, uncomfortable lining issues, and poor conditions of notions. Slit and Kaba (traditional dress for women in Ghana, the slit is an ankle length skirt and the kaba is a blouse) was the most frequently discarded custom-made garments among the respondents. It was recommended that in decreasing the rate of discard of custom-made garments, dressmakers should select appropriate stitches and notions for garment construction. They should ensure quality in the products they produce and check the fit of the garments properly before handing them over to clients to meet their expectations.